Ethical concepts. Consequentialism: pros and cons. (2nd November 2019) - Ellis, Peter
Abstract : We have previously explored the theory of consequentialism and pondered a little about how consideration of the consequences of an action might be used as a means of making ethical decisions. Here, we explore some of the pros and cons of using consequentialist methodology to guide our ethical decision-making processes in the kidney care unit